2019
DOI: 10.1149/09101.0235ecst
|View full text |Cite
|
Sign up to set email alerts
|

Solid Oxide Development Status at DTU Energy

Abstract: Solid oxide fuel cells and electrolysis (SOFC, SOE = SOC) are efficient technologies to link together energy sectors such as power, gas, and heat. They can thus emerge as key technologies in the current energy transitions towards systems based on renewable energy sources. DTU Energy has a long history of research in the areas of SOC and has currently an effort of ca. 35 person-years per year. The presentation will introduce the recent achievements ranging from materials development, cell & stack development, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…The long-term durability of SOECs and stacks has been extensively investigated in the past couple of decades. Most of the previously conducted long-term tests were carried out in galvanostatic mode [13][14][15][16][17][18] , i.e. current is kept constant while voltage is changing due to degradation or activation.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term durability of SOECs and stacks has been extensively investigated in the past couple of decades. Most of the previously conducted long-term tests were carried out in galvanostatic mode [13][14][15][16][17][18] , i.e. current is kept constant while voltage is changing due to degradation or activation.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the performance of the NH 3fed SOFC was similar to that of the H 2 -fed SOFC. In other SOFC configurations, similar phenomena can also be observed (10)(11)(12)(13)(14). Although past experimental results have proven that NH 3 and H 2 have similar electrochemical performance in SOFCs, more in-depth kinetics research on NH 3 -fed SOFCs is urgently needed.…”
mentioning
confidence: 74%
“…For example, utilizing variable resources such as wind and solar to provide low-cost and renewable electricity to drive electrolysis is desirable, but inherently leads to transient operation of the electrolysis device. Large changes in current or voltage can be tolerated by conventional SOECs [24], but rapid thermal transients are expected to be damaging. Temperature excursions can occur as instantaneous or daily variation in the electrical input and cause the SOEC to operate away from the thermo-neutral point in endothermic or exothermic regimes.…”
Section: The Opportunity For High-temperature Metal-supported Electromentioning
confidence: 99%